Stepping toward a Synodal Church - Osheim, Amanda C. (Theological studies, 2019)
In his address commemorating the fiftieth anniversary of the institution of the Synod of Bishops, Pope Francis expressed hope for a more synodal church. Consulting recent theological literature aids the discovery of potential-if only partial-steps towards a synodal church in three areas: spiritualities and structures of discernment; theological methodologies; and ecumenical gifts of synodality.